Gender Based Violence & Human Rights Violation In Sub-Saharan Africa: An Insight - Dr. Akhilesh Kumar Khan, Dr. Om Krishna (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Violence toward women is not a recent occurrence, nor are the effects to women's physical, emotional, and reproductive health. What is recent, however, is the increasing awareness that acts of violence against women are not isolated incidents, but rather part of a pattern of conduct that violates women's rights, restricts their social participation, and harms their health, prestige, and well-being. Women in Sub-Saharan Africa (SSA) are subjected to human rights violations that are unrivaled anywhere else in the world in the modern age. Intimate partner violence (IPV) continues to be the most significant component of violence against women, and is a widespread type of human and natural rights abuse. For women who are abused, intimate partner violence is linked to a variety of negative effects, including pregnancy loss and sexually transmitted infections. Nonetheless, African women continue to face economic, social, and cultural challenges, especially in the areas of healthcare, economic status, and basic education. The impact of violence on women's physical, sexual, reproductive, and mental health is detailed and highlighted in this paper. It also highlights some of the continent's gender equality initiatives, such as increased access to girls' education, an increase in the number of professionals and women in leadership roles, and the fact that women are now engaging in roles that were previously reserved for men. The study reveals that violence against women is widespread across the world. The results send a strong message around the world that violence against women is not a minor issue that occurs in isolated areas of society, but rather a global public health crisis that requires immediate intervention from all stakeholders.